Effect of Ethanol Extract of White Turmeric (Curcuma Zedoaria) as Hepatoprotector in Male Rats Induced By Cuso4 Pentahydrate - Sofiani Sari; Chrismis novalinda ginting; Linda chiuman; Sahna Ferdinan Ginting (Publikasi Indonesia, 2022)
White turmeric is known to the public as having various uses in terms of health, such as as a liver protector (hepatoprotector) which functions to destroy toxins that enter the human body, one of which is exposure to copper (CuSO4) Pentahydrate which is widely exposed in everyday life. to determine the protection against liver damage induced by copper by using ethanol extract of white turmeric rhizome (Curcuma Zedoaria) through histopathological examination of the liver of male wistar rats and to determine the best dose of white turmeric rhizome extract (Curcuma Zedoari). This study is categorized as an experimental research conducted following the posttest only control group design. Sampling is done through simple random sampling. After the data was proven to be normally distributed and continued with the ANOVA test and obtained a P value of 0.001 (? 0.05). The mean value of changes in the histological structure of the rat liver P1 0.00/0.00; P2 0.00/0.00; P3(500mg dose) 2.00/1.41; P4(750mg dose) 6.00/0.00; P5 4.44/1.50; P6(1000mg dose) 6.00/0.00. This shows that the highest degree of change in liver function is the P4 treatment group with an average of 6.00 and the lowest is the P6 treatment group with an average of 3.75. Conclusion: These results indicate that the ethanoic extract of white turmeric rhizome has high hepatoprotective activity at a dose of 1000mg.